2022
DOI: 10.3389/fcimb.2022.796656
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Bloodstream Infection in Immunosuppressed Patients: A 5-Year Retrospective Cohort Study

Abstract: IntroductionImmunosuppressed patients with bloodstream infection are at risk of mortality. Our objective was to assess the independent risk factors of bloodstream infection with mortality in immunosuppressive states.MethodsThe medical data of a total of 896 patients who were hospitalized in our hospital were collected from January 2015 to December 2019. Evaluation of the independent risk factors of mortality was done by univariate and multivariate logistic regression analyses.ResultsOf the 896 immunosuppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…This study showed that PCT was closely related to poor prognosis in immunosuppressed patients with CRGNB-BSI. Previous studies showed that increased PCT often suggests poor outcomes in both immunosuppressed patients with BSI and patients with CRGNB-BSI, 9 , 24 similar to the conclusion of our study. PCT is a predictor of poor prognosis in immunosuppressed patients with CRGNB infection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed that PCT was closely related to poor prognosis in immunosuppressed patients with CRGNB-BSI. Previous studies showed that increased PCT often suggests poor outcomes in both immunosuppressed patients with BSI and patients with CRGNB-BSI, 9 , 24 similar to the conclusion of our study. PCT is a predictor of poor prognosis in immunosuppressed patients with CRGNB infection.…”
Section: Discussionsupporting
confidence: 92%
“…Immunosuppressed patients are often admitted to the ICU due to multiple infections, and infectious complications lead to high mortality in immunosuppressed patients. 7 In previous studies, PCT and age were considered as independent risk factors for ICU admission, 9 consistent with the results of our study. Furthermore, it was found that use of tigecycline and development of AKI and septic shock could be prognostic predictors of ICU admission for immunosuppressed patients with CRGNB-BSI ( Table 4 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Immune suppression generally refers to low immune response to inflammation, and it is widely thought that a counter-inflammatory response aiming to inhabit overzealous inflammation may result in immune suppression. 1 This term is commonly used to qualify the immune status of patients with sepsis or systemic inflammatory response syndrome recently, which suggests that immune suppression indicates a status of immune failure making patients more vulnerable to the effects of diseases. 2 In general, typical immunosuppressed patients are usually transplant recipients and those with hematological malignancy, while atypical immunosuppression status may be present in patients with diabetes mellitus, liver cirrhosis, burns, and other diseases.…”
Section: Introductionmentioning
confidence: 99%